Sustainable Development Goals (SDGs): Approaches and practices with the school community on healthy, sustainable and inclusive spaces - Bezerra, Eliana Souza; Nascimento, Leandro Barros; Moreira, Rebecca Moura; Sígolo, Leticia Moreira; Toledo, Renata Ferraz de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The article intends to analyze approaches and practices of a social inclusion project developed among graduates and students from a technical school (ETEC) in the western zone of the city of São Paulo. The aforementioned project aimed at fostering shared and interdisciplinary construction of diverse knowledge and actions related to the 2030 Agenda, with the expectation of contributing to recognizing challenges in creating more sustainable, healthy and inclusive spaces within the school environment, as well as intervention possibilities in the territory. Based on the Research Itinerary developed by Paulo Freire, the Culture Circles, the project involved conducting workshops and training seminars led by graduates guided by PhD professors, in three stages: thematic investigation, coding/decoding, and critical unveiling. The initiative emerges as a response to society's growing demands for solutions to complex problems, contributing to the education of more conscious and engaged citizens, as well as professionals better prepared to deal with current issues. At the end of the project, while challenges were observed regarding the resources and spaces used for the meetings, it was also noticed that the ETEC students were able to make qualified observations and adopt an active stance towards the constructed space. Likewise, the graduates were able to link their individual research to the emerging socio-environmental demands present in the 2030 Agenda, strengthening active listening in light of the ecology of knowledge.
Keywords: 2030 Agenda; Culture Circles; Social Inclusion